University Academic Writing for International Students A Usage-based Approach - Moder, Carol Lynn; Avalos-Rivera, Alys; Horton, Ho'omana Nathan; Kinfe, Miriam; Sims, Paul; French, Seth; Zhao, Yelin (Open textbook library., 2020)
This resource is designed specifically to meet the academic writing needs of international students studying at universities in the United States. The materials in the book can be covered within a 14-week semester, but each chapter or section may also be used independently. Based on a series of needs analysis projects, this resource provides an overview of major rhetorical patterns of writing that are commonly used in university settings in the United States. These commonly required genres include descriptive and evaluative summaries, short essays, comparison and contrast assignments, literature reviews, descriptive reports, and proposals. The resource includes chapters that address the structure and purpose of these more common genres, including an awareness of the ways that the target audience and situation should shape the writing of each.